Between Legality and Justice: A Critical Study of the Supreme Court’s Judicial Reasoning in Dispute of the Awyu CustomaryForest - Achmad Hariri; A. Basuki Babussalam; Muhammad Aunurrochim Mas'ad Saleh (Universitas Muhammadiyah Surakarta, 2026)
Non-Indexed Publication